Acute and impaired wound healing: pathophysiology and current methods for drug delivery, part 1: normal and chronic wounds: biology, causes, and approaches to care - Demidova-Rice, Tatiana N; Hamblin, Michael R; Herman, Ira M (Advances in skin & wound care, 2012)
This is the first installment of 2 articles that discuss the biology and pathophysiology of wound healing, review the role that growth factors play in this process, and describe current ways of growth factor delivery into the wound bed. Part 1 discusses the latest advances in clinicians' understanding of the control points that regulate wound healing. Importantly, biological similarities and differences between acute and chronic wounds are considered, including the signaling pathways that initiate cellular and tissue responses after injury, which may be impeded during chronic wound healing.